PENINGKATAN PEMAHAMAN SISWA SMA NEGERI 6 PASARWAJO KABUPATEN BUTON TERHADAP MINUMAN BERALKOHOL - La Ode Muhammad Ricard Zeldi Putra; Mashendra Mashendra; Agusalim Agusalim; Ernawati Ernawati; Nasrin Nasrin (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Alcoholic drinks are drinks that contain ethanol. Ethanol is a psychoactive substance and its consumption causes loss of consciousness. According to WHO, alcohol is a psychotropic substance that is often abused. The abuse of alcohol in liquor in society is no longer the first incident to occur but has become a growing problem, especially among adolescents and tends to increase from year to year. Alcohol abuse also results in several forms of social problems such as fights, juvenile delinquency, immoral acts and even teenagers who then increasingly have no norms and tend to find it difficult to control their emotions. For example, for students of SMA Negeri 6 Pasarwajo, Buton Regency, the importance of socialization in terms of controlling and eradicating alcoholic beverages among students, especially at SMA Negeri 6 Pasarwajo, Buton Regency, in this study used the socialization method, namely counseling or giving explanations to students of SMA Negeri 6 Pasarwajo about impact of consuming liquor for students.